Efficacy and Safety of Tanshinone for Chronic Kidney Disease: A Meta-Analysis. (13th January 2020) - Zhou, Yao; Jiang, Shi-min; Li, Li; Wang, Ying; Ding, Lei; Liu, Chao-xia; Wu, Qi; Gao, Kun
Abstract : Objective . To systematically evaluate the efficacy and safety of tanshinone for chronic kidney disease (CKD). Methods . Randomized controlled trials (RCTs) on the treatment of CKD using tanshinone were searched using 4 Chinese databases (China National Knowledge Infrastructure (CNKI), Value In Paper (VIP), Wanfang, and Chinese Biology Medicine (CBM)) and 3 English databases (PubMed, Cochrane Library, and Excerpta Medica Database (Embase)). The results included data on blood urine nitrogen (BUN), serum creatinine (Scr), glomerular filtration rate (GFR), 24 h urine protein, microalbuminuria (mALB), β 2-macroglobulin ( β 2-MG), cystatin C (CysC), and safety events. The data were analyzed using Revman 5.3 and Stata 12.0 software. Results . Twenty-one studies were entered into this meta-analysis, which involved 1857 patients including 954 cases from the tanshinone treatment group and 903 cases from the control group. BUN levels in the tanshinone treatment group were significantly reduced compared with the control (standardized mean difference (SMD) = −0.65, 95% confidence interval (CI): −0.81 to −0.49, p < 0.01 ). In addition, subgroup analysis indicated that tanshinone had a significant effect in reducing Scr levels at 14, 21, and 28 days. Scr levels in the tanshinone treatment group were significantly reduced compared with the control group (SMD = −1.40, 95% CI: −2.09 to −0.71, p < 0.01 ); subgroup analysis based on treatment time also yielded the same results. GFR in the tanshinone treatment group was better than that in the control group (SMD = 0.83, 95% CI: 0.59 to 1.07, p < 0.01 ). In terms of urine protein levels, 24 h urine protein level, mALB, and β 2-MG of CKD patients were reduced to some degree compared with controls, and CysC levels in the tanshinone treatment group were also significantly reduced compared with the control group (SMD = −0.24, 95% CI: −0.44 to −0.03, p < 0.05 ). Safety in the tanshinone treatment group did not differ significantly from that of the control group (risk ratio (RR) = 7.78, 95% CI: 0.99 to 61.05, p > 0.05 ). Conclusion . This meta-analysis showed that tanshinone could control urine protein level in CKD patients, improve kidney function, and delay the evolution of CKD without significant side effects. However, the results were limited and should be interpreted with caution because of the low quality of the included studies. In the future, more rigorous clinical trials need to be conducted to provide sufficient and accurate evidence.